2020
DOI: 10.1016/j.ajog.2019.11.196
|View full text |Cite
|
Sign up to set email alerts
|

180: Salpingectomy at the time of cesarean delivery: A systematic review and meta-analysis

Abstract: fetal weight (EFW) improve the prediction of LGA infants when compared to using Hadlock EFW. STUDY DESIGN: This was a secondary analysis of data from a prospective study of women referred for growth ultrasounds during the 3 rd trimester. Growth trajectories (reported as change in Z-scores) for AC and EFW were derived from the difference in Z-scores between measurements at the time of anatomy survey (18-22 week) and third trimester ultrasound (26-36 weeks). Change in AC and EFW growth trajectories >90 th %ile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A recent systematic review and meta-analysis of OBS at the time of cesarean section in women who underwent permanent sterilization revealed that although the bilateral salpingectomy slightly increased the operative time, it was comparable to tubal ligation in terms of complications, completion rate, and short-term ovarian reserve with a greater cost-effectiveness ( 18 ) . Another larger and more recent systematic review and meta-analysis determined similar results in which OBS was not associated with more adverse outcomes than tubal ligation ( 19 ) . Providing those favorable data to the women who seek permanent contraception might have affected the high consent rates for OBS in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…A recent systematic review and meta-analysis of OBS at the time of cesarean section in women who underwent permanent sterilization revealed that although the bilateral salpingectomy slightly increased the operative time, it was comparable to tubal ligation in terms of complications, completion rate, and short-term ovarian reserve with a greater cost-effectiveness ( 18 ) . Another larger and more recent systematic review and meta-analysis determined similar results in which OBS was not associated with more adverse outcomes than tubal ligation ( 19 ) . Providing those favorable data to the women who seek permanent contraception might have affected the high consent rates for OBS in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…Interval partial salpingectomy has a 10-year failure rate of 20.1 per 1000, tubal occlusion (bands or clips) has a 10-year failure rate of 36.5 per 1000 and tubal desiccation has a 10-year failure rate of 7.5 or 24.8 per 1000 depending on whether monopolar or bipolar desiccation is used respectively [2]. Short term perioperative outcomes appear comparable for laparoscopic interval total BS and opportunistic total BS at time of caesarean section in comparison to bilateral tubal occlusion [18][19][20][24][25][26]. A recent systematic review and meta-analysis outlined the feasibility of BS at time of caesarean section as an alternative measure to tubal occlusion with few differences between the procedures with no difference in blood loss, length of hospital stay and perioperative complications [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is in agreement with the existing studies. Roeckner et al (2020) in a recent systematic review and metanalysis of salpingectomy at the time of cesarean delivery showed that bilateral salpingectomy at the time of cesarean delivery was not associated with an increased rate of surgical complications (8). Most of the other existing literature on BTS at the time of cesarean delivery are retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited well designed randomized controlled trials looking at prophylactic salpingectomy at the time of cesarean delivery. Roeckner et al (2020) in a systemic review and metanalysis of 3 randomized controlled trials and 8 retrospective studies, showed that salpingectomy at the time of cesarean delivery was associated with an increase in operative time without any increase in complications (8). Out of the three randomized controlled trials included in Roeckner et al's (2020) systemic review and metanalysis, Ganer-Herman et al (2017) did not performed a power calculation; Garcia et al (2018) was powered to assess the difference in operative times but used a bipolar vessel sealing device to perform the salpingectomies, and Subramaniam et al (2018) was under-powered (they needed 40 in each group but only had 27 bilateral salpingectomies and 38 bilateral tubal ligations) and the surgical providers performing the surgeries did not have any formalized training in performing total bilateral salpingectomies at the time of cesarean delivery (8-11).…”
Section: Introductionmentioning
confidence: 99%